2018
DOI: 10.1534/g3.118.200161
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Nuclear Exclusion of Hcm1 in AgingSaccharomyces cerevisiaeLeads to Vacuolar Alkalization and Replicative Senescence

Abstract: The yeast, Saccharomyces cerevisiae, like other higher eukaryotes, undergo a finite number of cell divisions before exiting the cell cycle due to the effects of aging. Here, we show that yeast aging begins with the nuclear exclusion of Hcm1 in young cells, resulting in loss of acidic vacuoles. Autophagy is required for healthy aging in yeast, with proteins targeted for turnover by autophagy directed to the vacuole. Consistent with this, vacuolar acidity is necessary for vacuolar function and yeast longevity. U… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 89 publications
1
15
0
Order By: Relevance
“…When viewed from this perspective, whether SGJ could exert the same effect on those BMSCs aged in vivo should be investigated further. However, many studies indicated that elements changed during aging, including autophagy, lysosomal function and activity, and v-ATPase activity, were not only found in vivo [ 1 , 15 , 38 , 44 ] but also in vitro [ 14 , 15 , 44 46 ]; therefore, according to our work, it is reasonable to draw a conclusion that SGJ is a potential lead compound for suppressing BMSC senescence. At least, it could be used as a powerful tool for studying and understanding the mechanism of aging.…”
Section: Discussionsupporting
confidence: 49%
“…When viewed from this perspective, whether SGJ could exert the same effect on those BMSCs aged in vivo should be investigated further. However, many studies indicated that elements changed during aging, including autophagy, lysosomal function and activity, and v-ATPase activity, were not only found in vivo [ 1 , 15 , 38 , 44 ] but also in vitro [ 14 , 15 , 44 46 ]; therefore, according to our work, it is reasonable to draw a conclusion that SGJ is a potential lead compound for suppressing BMSC senescence. At least, it could be used as a powerful tool for studying and understanding the mechanism of aging.…”
Section: Discussionsupporting
confidence: 49%
“…The loss of vacuolar acidity is an evolutionarily conserved aging phenotype identified thus far in yeast (Ghavidel et al, 2018;Hughes and Gottschling, 2012) and worms (Baxi et al, 2017). Future studies will need to directly assess whether loss of lysosomal acidity occurs in mammalian cell types with age or age-associated diseases, which could be testable using ratiometric pH sensors.…”
Section: Discussionmentioning
confidence: 99%
“…Imaging these cells in a microfluidic device with live-cell fluorescence imaging indicated that loss of vacuolar acidity begins essentially at the start of life (Figure 3a). By comparing different genetic strains, previous studies have indicated that loss of vacuolar acidity limits lifespan (Ghavidel et al, 2018;Hughes and Gottschling, 2012). To test whether vacuolar acidity was a risk factor for early death in a wildtype isogenic population, we monitored changes in vacuolar acidity during early life (ages 0-12 divisions).…”
Section: Aging Is Characterized By a Heterogeneous Loss Of Vacuolar Amentioning
confidence: 99%
See 1 more Smart Citation
“…These proton pumps maintain the acidity of the organelle by pumping the protons in the luminal part in an energy dependent manner, while its impairment has been found to increase the pH of the organelle [253]. Ageing in yeast has been found to be a major contributor of vacuolar alkalization, which is found to be caused by defective assembly of V-ATPases in lysosomal membranes [210].…”
Section: Autophagymentioning
confidence: 99%